"Tesla in Grünheide": Growing Intercultural Competence Through Role‐Play Simulation. Issue 2 (7th November 2022) - Joo, Hyoun‐A; Tuschling, Lina
Abstract: The development of intercultural communicative competence (ICC) becomes increasingly important in the world language curriculum and a crucial goal to prepare students for real‐life communicative situations outside of the classroom. This article discusses how a simulation exercise based on the contentious construction of the Tesla Gigafactory in Grünheide, Germany, facilitated the growth of students' ability to take perspectives other than their own – a crucial step toward ICC. Using the controversies about the Tesla Gigafactory as a real‐world case study, students participated in a role‐play simulation, set up as a town hall meeting, where they had to develop arguments whether Tesla should be given the official construction permit or not. This project‐based and student‐led exercise was designed to develop critical awareness of the cultural intricacy of the Tesla case by considering authentic dilemmas and conflicting perspectives. The activity was implemented in a virtual study abroad, advanced‐level German course. Comparing responses from a student feedback survey with Byram's ICC model (2021) suggests that the exercise helped students increase their factual knowledge, skills of interpreting, relating, discovering, and interacting, and develop differentiated understanding of other perspectives – important 21 st ‐century ICC skills for a global life and work environment.